A drug-free strategy to combat bacterial infections with magnetic nanoparticles biosynthesized in bacterial pathogens. Issue 5 (24th January 2022) - Kaushik, Swati; Thomas, Jijo; Panwar, Vineeta; Murugesan, Preethi; Chopra, Vianni; Salaria, Navita; Singh, Rupali; Roy, Himadri Shekar; Kumar, Rajesh; Gautam, Vikas; Ghosh, Deepa
Abstract : Pathogenic bacteria, both in vitro and in the host biosynthesize intracellular magnetic nanoparticles. The magnet-responsive pathogens can be destroyed using an alternating magnetic field. Abstract : The extensive and indiscriminate use of antibiotics in the ongoing COVID-19 pandemic might significantly contribute to the growing number of multiple drug resistant (MDR) bacteria. With the dwindling pipeline of new and effective antibiotics, we might soon end up in a post-antibiotic era, in which even common bacterial infections would be a challenge to control. To prevent this, an antibiotic-free strategy would be highly desirable. Magnetic nanoparticle (MNP)-mediated hyperthermia-induced antimicrobial therapy is an attractive option as it is considered safe for human use. Given that iron and zinc are critical for bacterial virulence, we evaluated the response of multiple pathogenic bacteria to these elements. Treatment with 1 mM iron and zinc precursors resulted in the intracellular biosynthesis of MNPs in multiple Gram-positive and Gram-negative disease-causing bacteria. The superparamagnetic nanoparticles in the treated bacteria/biofilms, generated heat upon exposure to an alternating magnetic field (AMF), which resulted in an increase in the temperature (5–6 °C) of the milieu with a subsequent decrease in bacterial viability. Furthermore, we observed for the first time that virulent bacteria derived from infected samples harbour MNPs, suggesting that the bacteria had biosynthesised the MNPs using the metal ions acquired from the host. AMF treatment of the bacterial isolates from the infected specimens resulted in a strong reduction in viability (3–4 logs) as compared to vancomycin/ciprofloxacin treatment. The therapeutic efficacy of the MNPs to induce bacterial death with AMF alone was confirmed ex vivo using infected tissues. Our proposed antibiotic-free approach for killing bacteria using intracellular MNPs is likely to evolve as a promising strategy to combat a wide range of bacterial infections.